Microstructural effect of different concentrations of hydrogen peroxide photoactivated with LED/laser - Manzoli, Tatiane Miranda [UNESP] (2023)
Background: The use of different concentrations of hydrogen peroxide (HP) photoactivated with LED/laser sources is common however, their influence on tooth structure is not yet fully elucidated. This study aimed to evaluate the pH, microhardness and surface roughness of different bleaching protocols photoactivated with LED/laser. Methods: Forty bovine incisors were sectioned (7 × 7 × 2 mm) and randomized into four groups for analysis of pH (n = 5), microhardness and roughness (n = 10): HP35, HP6_L, HP15_L, HP35_L. The pH analysis was performed in the initial and final minute of the bleaching protocol. Microhardness and roughness were evaluated before and 7 days after the last bleaching session. Results were obtained from two-way ANOVA for repeated measures and Bonferroni post-test at a significance level of 5%. Results: HP6_L showed higher pH and greater stability between the initial and final evaluations, while the other groups showed similar pH with reduced values in the intragroup evaluation. No differences between groups in microhardness and roughness evaluations were observed. Conclusions: Although HP6_L showed higher alkalinity and pH stability, none of the protocols reduced the microhardness and surface roughness of bovine enamel.